The Education of Indonesian Shiâi Leaders - Zulkifli, Z. (Al-Jamiah: Journal of Islamic Studies, 2009)
Amidst the Sunni majority in Indonesia, there exist a small number of Shi`i adherents that have increased quantitatively and qualitatively since the Iranian revolution of 1978-1979. To see the Shi`i community as a monolithic entity is misleading. In fact, this community is comprised of several groups that may not be united under a recognised single leader. Leadership in a community results partly from education, although the degree and extent of its influence remain questionable. In this regard, this article aims at analysing the education of Shi`i leaders in Indonesia. What types of education did they experience? In terms of education backgrounds, Shi`i leaders may be classified into the ustadhs and intellectuals. The ustadhs are those educated in institutions of Islamic learning and the majority are alumni of hawza âilmiyya (colleges of Islamic learning) in Qum, Iran. Since the establishment of the Islamic RepublicÂ  of Iran in 1979, the number of Indonesian students studying in Qum has increased significantly and the hawza âilmiyya of Qum have been very important in producing the Shi`i ustadh in Indonesia. On the other hand, the intellectuals are those who have graduated from secular universities but received religious instruction in non-formal education institutions. Although education is an important factor contributing to leadership, other factors have to be considered such as scholarship in religious sciences, involvement in daâwa and education activities, leadership experience in education and socio-religious institutions, as the case of Jalaluddin Rakhmat has shown.